"He is not crying for real": severe, multiple disabilities and embodied constraint in two special-needs education units. Issue 1 (1st January 2017) - Evensen, K. V.; Ytterhus, B.; Standal, Ø. F.
ABSTRACT: Students with severe and multiple disabilities are, according to official Norwegian policies, to be included in ordinary school settings. Yet usually their schooldays are organized differently from those of their non-disabled peers. In this paper the authors aim (1) to identify how embodied meaning unfolds when students with severe and multiple disabilities are fastened in assistive technical devices and (2) to identify how staff respond when students make gestures. Applying the phenomenological philosophy and the phenomenological methodology the authors acknowledge movement as fundamental for the students' possibilities to express their perspective. Their empirical material describes how possibilities for making gestures are severely limited when students are fastened in devices. To shed light on the staff's recognition and response as fundamental for interactions when students are under embodied constraint, they have applied Goffman's interactionism.